용액 공정 기반의 인듐 아연 산화물 트랜지스터의 PMMA 보호막 여부에 따른 신뢰성 평가 - 허관준; Kwan Jun Heo; 엄주송; Ju Song Eom; 조현아; Hyeonah Jo; 최성곤; Seong Gon Choi; 정병준; Byung Jun Jung; 김성진; Sung Jin Kim (대한금속·재료학회지, 54(4), 2016)
We investigated poly(methyl methacrylate) (PMMA) passivation of solution-processed indium zinc oxide (IZO) thin-film transistors (TFTs). PMMA provides solution-processability and good barrier characteristics against environmental elements such as water and oxygen. The PMMA passivation layers protect the IZO active layer of the TFTs without deteriorating their performance during gate bias stress measurements under ambient conditions, and improve their electrical properties by decreasing leakage current. Moreover, the potential to safely manipulate IZO-TFTs after PMMA passivation was proven by realizing a simple n-channel resistive-load inverter.